2012
DOI: 10.1111/j.1440-1843.2011.02108.x
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in bronchoscopic imaging

Abstract: Bronchoscopy is a minimally invasive method for diagnosis of diseases of the airways and the lung parenchyma. Standard bronchoscopy uses the reflectance/ scattering properties of white light from tissue to examine the macroscopic appearance of airways. It does not exploit the full spectrum of the optical properties of bronchial tissues. Advances in optical imaging such as optical coherence tomography (OCT), confocal endomicroscopy, autofluorescence imaging and laser Raman spectroscopy are at the forefront to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 68 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…As a newly developed technology, autofluorescence bronchoscopy shines some light, albeit not strongly, on this problem. It allows rapid scanning of large areas of the bronchial surface for subtle abnormalities that are not visible on WLB 34. However, in comparison with conventional WLB, some autofluorescence bronchoscopy systems have increased sensitivity but significantly reduced specificity 8–13.…”
Section: Discussionmentioning
confidence: 99%
“…As a newly developed technology, autofluorescence bronchoscopy shines some light, albeit not strongly, on this problem. It allows rapid scanning of large areas of the bronchial surface for subtle abnormalities that are not visible on WLB 34. However, in comparison with conventional WLB, some autofluorescence bronchoscopy systems have increased sensitivity but significantly reduced specificity 8–13.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that vessel density was decreased in the smokers as compared to the non-smokers, concluding that smoking would affect not only lung parenchyma but also systemic angiogenesis (32). A B the properties of light waves, with microscopic resolution (1-20 µm) and a penetration depth of maximum 2-3 mm that allows high-definition cross-sectional images of the airway luminal wall (33). Although the OCT system is analogous to that of B-mode ultrasound, the procedure requires no contact between the small optical probe and the tissue and it is able to delineate, in real time, cellular and extracellular structures at a resolution that is 20 times as high as that of ultrasound (34).…”
Section: Hmbmentioning
confidence: 99%
“…68 The confocal laser endoscopy system (Cellvizio; Mauna Kea Technologies, Paris, France) uses lasers at specific wavelengths (488 or 660 nm) to excite tissue fluorescence with or without local contrast for microimaging of the respiratory tract (Fig. 5).…”
Section: Pet Response Criteria In Solid Tumorsmentioning
confidence: 99%